O Estudo de Impacto de Vizinhança (EIV) e seu potencial como ferramenta de planejamento - Gerson José de Mattos Freire (2015)
This thesis deals with Neighborhood Impact Study (EIV), a multidisciplinary analysis standardized by the City Statute and necessary for the installation of impact projects in urban areas, seeking to demonstrate aspects that could increase their efficiency and usefulness to society and to the urban planning. In it are presented and discussed the modalities for the Environmental Impact Assessment (AIA), their concepts and historical evolution in Brazil and other countries. It describes the role of AIA in urban planning, how the EIV originates in the Environmental Impact Assessment and is designed to ensure the quality of urban life, adapting himself to the study of positive and negative effects of projects or modifying actions on the resident population in the area and its vicinity. It highlights the preliminary authorization role of EIV in Brazil and how the AIA are used in Europe, associated with territorial planning actions. The legal requirements for the preparation of the EIV are analyzed, considering the types of projects to which they apply in Brazilian state capitals and the Federal District and the differences between the municipal regulations for the preparation, content and analysis of EIV, highlighting still questions about public participation in the decision-making process. The study presents methodologies that increase the quality of the prognosis and diagnosis of EIV and how the combined use of spatial analysis techniques, perception surveys and scenario building can increase its efficiency, evaluating ways to add results of the EIV as qualifiers elements of urban indicators of quality and sustainability. The application of the proposed techniques is exemplified by means of analysis of the Urban Operation Antonio Carlos / Pedro I / Leste-Oeste, in Belo Horizonte, specifically looking to know the anthropogenic relationships present in Lagoinha sector through the application of perception survey of the resident population on issues related to the neighborhood, the enterprise and the expected impacts. The results are compared with those presented in EIV conducted for the project, discussed under the territorial point of view and presented in the form of neighborhood qualifying indexes. The impacts identified in the survey are used as elements for the elaboration of retrospective scenarios.